Barriers to health care contribute to delays in follow‐up among women with abnormal cancer screening: Data from the Patient Navigation Research Program. Issue 22 (19th August 2015) - Ramachandran, Ambili; Snyder, Frederick R.; Katz, Mira L.; Darnell, Julie S.; Dudley, Donald J.; Patierno, Steven R.; Sanders, Mechelle R.; Valverde, Patricia A.; Simon, Melissa A.; Warren‐Mears, Victoria; Battaglia, Tracy A.; ,
Abstract : BACKGROUND: There is limited understanding of the association between barriers to care and clinical outcomes within patient navigation programs. METHODS: Secondary analyses of data from the intervention arms of the Patient Navigation Research Program were performed, which included navigated participants with abnormal breast and cervical cancer screening tests from 2007 to 2010. Independent variables were: 1) the number of unique barriers to care (0, 1, 2, or ≥3) documented during patient navigation encounters; and 2) the presence of socio‐legal barriers originating from social policy (yes/no). The median time to diagnostic resolution of index screening abnormalities was estimated using Kaplan‐Meier cumulative incidence curves. Multivariable Cox proportional hazards regression examined the impact of barriers on time to resolution, controlling for sociodemographics and stratifying by study center. RESULTS: Among 2600 breast screening participants, approximately 75% had barriers to care documented (25% had 1 barrier, 16% had 2 barriers, and 34% had ≥3 barriers). Among 1387 cervical screening participants, greater than one‐half had barriers documented (31% had 1 barrier, 11% had 2 barriers, and 13% had ≥3 barriers). Among breast screening participants, the presence of barriers was associated with less timely resolution for any number of barriers compared with no barriers. Among cervical screening participants, only the presence of ≥2 barriers was found to be associated with less timely resolution. Both types of barriers, socio‐legal and other barriers, were found to be associated with delay among breast and cervical screening participants. CONCLUSIONS: Navigated women with barriers resolved cancer screening abnormalities at a slower rate compared with navigated women with no barriers. Further innovations in navigation care are necessary to maximize the impact of patient navigation programs nationwide. Cancer 2015;121:4016–4024. © 2015 American Cancer Society . Abstract : Among women who received navigation for abnormal breast or cervical cancer screening in the Patient Navigation Research Program, those with barriers appear to resolve cancer screening abnormalities at a slower rate compared with those with no barriers. The negative effect on timeliness of care was observed regardless of the given number of barriers or the type of barrier.